Survival and prognostic factors in pediatric osteosarcoma: A 5-year single-center experience in Central Java, Indonesia - Riza, Muhammad; Salimo, Harsono; Wasita, Brian; Idulhaq, Mujaddid; Saputra, Rhyan Darma; Widyaningsih, Vitri; Soestrisno, Soestrisno; Zahidah, Fairuz; Wayanshakty, Janur (Indonesian Pediatric Society, 2024)
Background The advent of chemotherapy with multimodal treatment has improved the survival rate of osteosarcoma. However, the survival rate of patients with osteosarcoma in low- and middle-income countries (LMICs) remains lower than in high-income countries (HICs). Objective To assess prognostic factors associated with survival rate of pediatric patients with osteosarcoma in Moewardi Hospital, Surakarta. Methods This retrospective study was performed in pediatric osteosarcoma patients at Moewardi Hospital, Surakarta from 2018 to 2022. We described patients’ clinical presentations and assessed prognostic factors. Survival rate was calculated using Kaplan–Meier survival analysis. Prognostic factors were analyzed using univariate and multivariate Cox regression methods. Results Of the 82 patients included in the study, 40 (48.8%) were male and 42 (51.2%) were female. Most subjects (75.6%) were diagnosed with osteosarcoma at the age of >10 years, 45 patients (54.9%) had primary tumors in the femur, and 16 patients (19.5%) had limb salvage surgery. The mean event-free survival duration was 13.6 (95%CI 9.7 to 17.5) months. The mean duration of overall survival was 22.7 (95%CI 17.3 to 28.1) months, with a 44.1% survival probability. Type of surgery was a significant prognostic factor (P=0.018), with limb salvage having better survival probability (93.3%) than amputation (19.8%). Conclusion The overall survival rate of osteosarcoma patients at our center is still lower than in other regional centers. Limb salvage surgery was a significant prognostic factor for survival, while gender, location of primary tumor, histological subtype, and metastasis at the time of diagnosis were not.